Peranan Badan Kesatuan Bangsa dan Politik (Kesbangpol) Dalam Menangani Daerah Rawan Konflik di Kota Medan - Wirman Wirman; Havez Ababil (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
This study focuses on how the role of the entity of the Nation and Political of the City of Medan in handling conflict prone areas based on various problems or conflicts occurring in Medan City. This study aims to determine whether the role of the entity of the nation and the political entity of the city of Medan has been running well or not yet as well as analyzing what factors are inhibiting in handling conflict prone areas and knowing the effort to overcome these obstacles. The research method used is qualitative method with descriptive approach. The data collection technique used by researchers in conducting this study is observation, interview and also documentation. This study shows that the role of the Union and Political Unity of the United States in handling conflict prone in the territory of Medan has been done maximally despite obstacles in the process of its organizations. The Nation and Political Unity Agency has had an effort to overcome such obstacles to maximize the handling of conflict prone in the territory of Medan. Keywords: Role, Nation and Unit Agency, Conflict House Region